Religion, Health, Social Capital and Place: The Role of the Religious, Social Processes and the Beneficial and Detrimental Effects on the Health and Wellbeing of Inhabitants in Deprived Neighbourhoods in Malta - Satariano, Bernadine (Journal of religion and health, 2020)
This paper emphasises the important role that place has in determining how religious social processes operate and impact on health and wellbeing. It draws upon evidence through qualitative in-depth interviews with families (both parents and children) living in two deprived neighbourhoods in Malta, a "traditional" and a "modern" one. It emerged that religious faith and practices can generate normative and resource-based social capital which can positively impact on health and wellbeing. However, some individuals found this social capital constraining and this had detrimental effects on their wellbeing. The context, composition, history and norms of the place emerge as highly important. This study emphasises that religious social processes operate in a highly complex manner, and "adherents" and "disaffiliates" are likely to enjoy positive or negative health and wellbeing according to where they live and according to important persons living in the neighbourhood such as the parish priest. This study contributes to the research gap between religion, social capital and health and the complex, social processes that operate at the local level of place.